Krisis Ekonomi Global dan Isu Kenaikan BBM dalam Prespektif Akuntansi, Politik, Kebijakan Fisikal dan Perencanaan Pembangunan Daerah Kabupaten Pulau Morotai - Yuliana Y; Ardin Umar; Jamiludin Hasan (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
The global economic crisis, coupled with fluctuations in fuel prices, has placed immense pressure on archipelagic and border regions such as Morotai Island Regency. As a designated Special Economic Zone (SEZ), Morotai reliance on external logistics supplies renders it highly vulnerable to inflation. This community service initiative aims to provide education, policy advocacy, and the formulation of integrative strategies based on four key perspectives: accounting, politics, fiscal policy, and regional development planning. The implementation method utilized public dialogue. The results indicate an improved understanding among students regarding budget efficiency, the strengthening of local-scale fuel distribution oversight regulations, and the reformulation of central-to-regional transfer funds for social safety nets.